ENHANCING COMPUTATIONAL EFFICIENCY OF STRESS CONSTRAINED TOPOLOGY OPTIMIZATION - GEBREMEDHEN, HAILU SHIMELS (2018)
Structural topology optimization is a mathematical approach which seeks optimal material distribution for a given design domain under defined loading and boundary conditions. It has been formulated and solved either to minimize compliance or weight under volume and stress constraints, respectively.